Rancang Bangun Pengering Gabah Menggunakan Panas Hasil Pembakaran Limbah Sekam - Rahman, Fadhli; Haslinah, Andi; Illang, M. Paisal; Aslan, Aslan (Department of Electrical Engineering, University of Patria Artha, 2021)
Most of the drying process in Indonesia still relies on the direct drying method in the sun, the method is simple depending on weather conditions, requires large land and takes 3 to 4 days dry. So that artificial dryers began to be used, but only large factories resulted in small farmers not being able to experience technological developments in agriculture, from this condition inspired us to design grain dryers using heat from burning waste husks, to provide various processing conveniences. Farmers work in processing crops. The stages that we do in this research are system design, tool design, tool testing, and validation so that it can produce tools that work optimally. As for the test results, the initial weight of harvested grain is 35 kg, moisture content of the rainy season is 25% by keeping the drying room temperature at 55℃ and takes 240 minutes. To achieve a moisture content of 14%. milled water content. heat transfer by forced convection with a heat transfer rate of 11.2 ms, an area of 80 m² with a film temperature of 34.5°C, the value of the heat transfer coefficient 0.004137 Wm²℃.